Prevalence of the mutations responsible for glanzmann thrombasthenia in horses in Brazil - Leite, Raíssa O. [UNESP]; Ferreira, Júlia F. [UNESP]; Araújo, César E. T. [UNESP]; Delfiol, Diego J. Z.; Takahira, Regina K. [UNESP]; Borges, Alexandre S. [UNESP]; Oliveira-Filho, Jose P. [UNESP] (MDPI, 2019)
Glanzmann’s thrombasthenia (GT) is an autosomal recessive inherited disorder characterized by changes in platelet aggregation, leading to hemorrhage and epistaxis. To date, two independent mutations have been described in horses and associated with this disorder, a point mutation (c.122G > C) and a 10-base-pair deletion (g.1456_1466del) in the Integrin subunit alpha2β gene (ITGA2B) of horses of different breeds (Quarter Horse, Thoroughbred, Oldenburg, and Peruvian Paso). ITGA2B codifies the αIIb subunit of the αIIbβ3 integrin, also termed platelet fibrinogen receptor. Horses with GT have been diagnosed in the USA, Canada, Japan, and Australia. However, there are no studies on the prevalence of GT in horses. The aim of this study is to evaluate the prevalence of the mutations responsible for GT in horses in Brazil. A total of 1053 DNA samples of clinically healthy Quarter Horse (n = 679) and Warmblood horses (n = 374) were used. DNA fragments were amplified by PCR and sequenced. The genotype of each animal was analyzed and compared to the nucleotide sequence of the ITGA2B gene found on GenBank™. There were no carriers in the analyzed samples, that is, all animals tested were wild type. Therefore, under the conditions in which this study was carried out, it can be inferred that GT seems to be extremely rare in the population of Quarter Horses and Warmbloods in Brazil, although it is not possible to affirm that there are no horses carrying mutated alleles in Brazil.
Keywords: Epidemiology; Fibrinogen receptor; Genetic disease; Prevalence study